DAMPAK NEGATIF GAME ONLINE TERHADAP PERUBAHAN PERILAKU SOSIAL SISWA SEKOLAH DASAR - Paradila Hafidz; Rizki Wahyu Saputri; Andhita Risko Faristiana (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
Online games are a form of advancement in technological development. In its development, online games have had several impacts on today’s generations. Some of the effects are changing the behavior of a child, feeling lazi to learn, reducing social life, and stretching closeness to parents. The purpose of this study is to determine changes in behavior that occur in elementary school children due to online games. This research is a type og qualitative research using qualitative descriptive methods The subjects of this study were grade V students of SDN Tamanasri 2, Pringkuku sub-district, Pacitan regency. Data collection in the study was carried out using observation methods and distributing questionnaires to resource persons. Also by linking previous research. The results of the study showed that all students were users of online games and felt the negative impact of the game.